Socio-demographic, lifestyle and health characteristics among snus users and dual tobacco users in Stockholm County, Sweden - Galanti Maria; Magnusson Cecilia; Engström Karin (BMC, 2010)
Abstract Background Socio-demographic and lifestyle characteristics of snus users have not been systematically described. Such knowledge is pivotal for tobacco control efforts and for the assessment of health effects of snus use. Methods A cross-sectional study was conducted, based on the Stockholm Public Health Survey, including a population-based sample of 34,707 men and women aged 18-84 years. We examined how socio-demographic, lifestyle and health-related characteristics were associated with the prevalence of current daily snus use, smoking and dual tobacco use. Logistic regression was used to calculate odds ratios of prevalence (ORs) and 95% confidence intervals (CIs). Results Low educational level (OR = 1.60, CI = 1.41-1.81 and OR = 1.49, CI = 1.17-1.89, for men and women respectively), as well as occupational class and low income were associated with snus use. Some unfavourable lifestyle characteristics, including risky alcohol consumption (males: OR = 1.81, CI = 1.63-2.02; females: OR = 1.79, CI = 1.45-2.20), binge drinking and low consumption of fruit and vegetables were also associated with snus use. In contrast, physical inactivity and overweight/obesity were not, nor was perceived health. The prevalence of smoking followed steeper gradients for social as well as lifestyle characteristics. Overweight and obese men were however less often smokers. Perceived poor general health and psychological distress were highly related to smoking. Social disadvantage, as well as unhealthy lifestyle and self-reported poor health were strongly associated with dual use. There were limited differences between men and women. Conclusions The social, lifestyle and health profiles of exclusive snus users in Stockholm County are less favourable than those of non-users of tobacco, but more advantageous than those of exclusive smokers. This knowledge should guide tobacco control measures as well as the interpretation of health risks linked to snus use.